Ship Cargo Compartment Environment Measurement and Control System Based on SSM Framework - Hu, Weijie; Ren, Hongxiang; Wang, Mingyang (IOP conference series. Earth and environmental science, 2019)
In order to reduce the cargo damage during the transportation of ocean-going ships and ensure the safety of ship personnel entering the cabin, a ship cargo tank environment monitoring and control system based on SSM framework is proposed. The high-precision sensor is used to collect the environmental information in the cargo hold of the ship, transmit it to the local client, integrate the Socket monitor interface into the SSM framework, establish the communication between the local client and the cloud server, and realize the environmental parameter detection and exhaust control of the cargo hold of the ship. The Web project development model using MVC software architecture makes the ship cargo compartment environmental monitoring and control system more convenient in storage and display. The test results show that the system can effectively monitor and control the environmental parameters of the cargo tank of the ship.